Genomic insights and epidemiology of mcr-1-Carrying Escherichia albertii isolated from agricultural soil in China - Yu Yang; Wenhong Liu; Zanzan Zhao; Kexin Guo; Xinrui Wang; Zhenghao Lou; Xiaolu Yang; Lu Gong; Kun Wang; Xiaojing Liu; Hao Xu; Qiyu Liu; et al. (BMC Genomics)
Abstract Background Polymyxins are critical in treating multidrug-resistant Gram-negative bacteria infections, yet their overuse has spurred the emergence of polymyxin-resistant pathogens globally. This study aims to analyze the genomic characteristics of the Escherichia albertii strain 6S-65-1 carrying the mcr-1 gene and to investigate the global epidemiology of mcr-1-carrying E. albertii strains. Results In this study, we identified and analyzed a polymyxin-resistant Escherichia albertii strain (6S-65-1) carrying the mcr-1 gene, isolated from agricultural soil in China. Whole-genome sequencing and comparative genomic analyses revealed two chromosomal integrations of the mcr-1 gene within Tn6330 transposon structures, indicating its capacity for horizontal gene transfer. Strain 6S-65-1 also harbors other antimicrobial resistance genes, including tet(A) , sul3, and aph (3')-Ia, enhancing its resistance profile. Comparative genomic analysis of E. albertii genomes in the NCBI database revealed that mcr-1-carrying E. albertii strains are geographically restricted to China and Japan, and have been isolated from both animals and humans. Phylogenetic analysis revealed that strain 6S-65-1 was most closely related to a human-derived strain from Japan (SAMD00164101), with both strains carried virulence genes (cdt, paa, and eae) that enable them to form attaching and effacing (A/E) lesions. Among all publicly available ST4619 E. albertii genomes, strain 6S-65-1 is the first to carry the mcr-1 gene. Conclusion Our findings offer new insights into the epidemiology and genomic features of mcr-1-carrying E. albertii, underscoring the need for targeted management strategies to curb its spread. These findings underscore the importance of “One Health” approaches to antimicrobial resistance, which require coordinated efforts across human, animal and the environmental health sectors.